RELIEF AND LITHOLOGICAL AND GEOMORPHOLOGICAL STRUCTURE OF THE TERRITORY - AS FACTORS OF SOIL EROSION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The northeastern part of the Namangan region is one of the largest, ancient agricultural regions of the Fergana Valley. There are Namangan, Kasansay, Yangikurgan-Pishkaran and other oases. The region is bounded in the north and east with Kyrgyzstan in the south - by the Naryn-Syrdarya river in the west - by the Kasansay river. The total area of the territory is 1860 km2, stretching from south to north - 75 km and from west to east - 50 km.